Diagnostic value of hybrid perfusion SPECT/CT and CTPA for detection of pulmonary embolism - Sevda Naydenska; Konstantin Grudkov; Daniela Petrova; Dora Zlatareva; Bilyukov Radoslav; Daniela Krasimirova; Ventsislava Pencheva (Biotechnology & Biotechnological Equipment)
The diagnosis of pulmonary embolism (PE) employs a combination of clinical assessment, D-dimer assay and imaging with pulmonary ventilation-perfusion (V/P) scintigraphy and/or computed tomography pulmonary angiography (CTPA). It is generally accepted that V/P SPECT and CTPA have high diagnostic accuracy. Nonetheless, there are only limited data directly comparing these two modalities. This prospective cross-sectional study included 184 hospitalized patients with clinically suspected PE. Clinical assessment, electrocardiography (ECG), vein ultrasound, echocardiography, arterial blood gas test, D-dimer assay, perfusion single photon-emission computed tomography/computed tomography (P-SPECT/CT) and CTPA were carried out. PE was diagnosed in 109 of 146 patients (74.66%) by P-SPECT/CT and 47 of 89 patients (52.81%) by CTPA. The sensitivity and specificity of P-SPECT/CT were 82.9%, respectively, 64.7%. The positive predictive value of SPECT/CT was 94.7%, the negative predictive value was 33.3% and the validity was 80.8%. For CTPA the sensitivity was 58.2% and specificity 90%. The positive predictive value of CTPA was 97.9%, the negative predictive value 21.4% and the accuracy (performance) 61.8%. There was no significant difference between the two methods regarding the diagnosis of PE at sub-segmental and segmental level. The sensitivity of P-SPECT/CT was significantly higher compared with CTPA, whereas the specificity was significantly higher at CTPA for diagnosis of PE. The P-SPECT/CT showed excellent diagnostic performance with high sensitivity and a very high positive predictive value. Thus, it could serve as first-line imaging for PE in the number of prevalent cases.